2017
DOI: 10.1007/s12308-017-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of xeroderma pigmentosum genes (XPC, XPD, and XPG) and susceptibility to acute leukemia among a sample of Egyptian patients

Abstract: DNA repair systems play a key role in protecting the DNA from damage caused by different endogenous and environmental factors. Genetic polymorphisms in DNA repair genes may lead to increased cancer susceptibility including leukemia. Due to different environmental genetic interactions among each population, the aim of the current study was to assess the association between three genetic polymorphisms of xeroderma pigmentosum complementation group: XPD (rs13181), XPC (rs2228001), and XPG (rs17655) and the suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In the present study, variant genotypes of XPG 3507G>C were not associated with the risk of developing MPN. Our findings are consistent with those reported by ElMahgoub following a study of 50 Egyptian patients with acute leukemia [ 13 ]. As a similarity, Ruiz-Cosano et al, following a study of 213 cases and 214 controls, reported that XPG 3507G>C polymorphism was not associated with the risk of lymphoma (OR = 1.1; 95% CI = 0.8–1.7) [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, variant genotypes of XPG 3507G>C were not associated with the risk of developing MPN. Our findings are consistent with those reported by ElMahgoub following a study of 50 Egyptian patients with acute leukemia [ 13 ]. As a similarity, Ruiz-Cosano et al, following a study of 213 cases and 214 controls, reported that XPG 3507G>C polymorphism was not associated with the risk of lymphoma (OR = 1.1; 95% CI = 0.8–1.7) [ 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…Blood samples were used for genomic DNA extraction performed with the Quick-gDNA MiniPrep kits (Zymo Research, Irvine, CA, USA) and PureLink Genomic DNA Mini kits (Invitrogen, Carlsbad, CA, USA). The polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) method was used in establishing the genotypes of XPC 1496C>T, XPC 2920A>C, XPD 2251A>C, XPF -673C>T, XPF 11985A>G, and XPG 3507G>C, as previously described [ 13 , 27 , 37 , 46 , 47 , 48 ]. After the PCR reaction, digestion was performed with specific restriction enzymes (Thermo Fisher Scientific, Waltham, MA, USA), followed by agarose gel electrophoresis (2%) ( Table 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by ElMahgoub IR et.al, which evaluated polymorphisms of xeroderma pigmentosum genes (XPC, XPD, and XPG) and susceptibility to acute leukaemia among a sample of Egyptian patients, homovariant for XPD had four fold increased risk of developing AML (OR = 4.4, P = 0.025) either alone or with variant genotypes of XPC and XPG. 6 The published cases of XP with haematological malignancies are summarised in table 1. Most of the patients were adolescents, with the youngest being a 7 year old with B-ALL with MDS.…”
Section: Discussionmentioning
confidence: 99%
“…Xeroderma Pigmentosum group C) gene belongs to the Nucleotide Excision Repair (NER) pathway; this gene encodes a protein binding damaged DNA in apoptosis and in the rst phases of DNA repair [27]. The Lys939Gln polymorphism of this gene consists in an A > C transition at codon 939 of exon 15; this polymorphism has been studied in relation to the probability of developing many cancer types, with inconsistent results [27,28,29].…”
Section: Introductionmentioning
confidence: 99%